Turn Taking Strategies in Hot Ones Show with Zayn Malik (PANOPTICON: Journal of English Studies, 2024)
This study examines a conversation by analyzing the dynamics of turn-taking within it. The focus of the study is on a talk show from the Hot Ones program, featuring guest star Zayn Malik, posted on the YouTube channel. A qualitative approach is used to explore how the host and guests manage turn-taking to facilitate effective communication. The theoretical framework of Sacks et al. (1974) serves as the foundation for this study. The findings reveal the following turn-taking strategies: starting up (17), holding the floor (22), interrupting (12), overlapping (1), yielding the floor (2), and taking over (1). The analysis of turn-taking, particularly the prevalence of holding the floor, highlights key conversational strategies in talk shows. Through detailed examination of the video podcast data, new insights into the structure and dynamics of conversation, including various turn-taking strategies, are uncovered.